Versatility of targeted antibiotic-loaded gold nanoconstructs for the treatment of biofilm-associated bacterial infections. (17th February 2018) - Meeker, Daniel G.; Wang, Tengjiao; Harrington, Walter N.; Zharov, Vladimir P.; Johnson, Sarah A.; Jenkins, Samir V.; Oyibo, Stephanie E.; Walker, Christopher M.; Mills, Weston B.; Shirtliff, Mark E.; Beenken, Karen E.; Chen, Jingyi; et al.
Abstract: Background: We previously demonstrated that a photoactivatable therapeutic approach employing antibiotic-loaded, antibody-conjugated, polydopamine (PDA)-coated gold nanocages (AuNCs) could be used for the synergistic killing of bacterial cells within a biofilm. The approach was validated with a focus on Staphylococcus aureus using an antibody specific for staphylococcal protein A (Spa) and an antibiotic (daptomycin) active against Gram-positive cocci including methicillin-resistant S. aureus (MRSA). However, an important aspect of this approach is its potential therapeutic versatility. Methods: In this report, we evaluated this versatility by examining the efficacy of AuNC formulations generated with alternative antibodies and antibiotics targeting S. aureus and alternative combinations targeting the Gram-negative pathogen Pseudomonas aeruginosa . Results: The results confirmed that daptomycin-loaded AuNCs conjugated to antibodies targeting two different S. aureus lipoproteins (SACOL0486 and SACOL0688) also effectively kill MRSA in the context of a biofilm. However, our results also demonstrate that antibiotic choice is critical. Specifically, ceftaroline and vancomycin-loaded AuNCs conjugated to anti-Spa antibodies were found to exhibit reduced efficacy relative to daptomycin-loaded AuNCs conjugated to the same antibody. In contrast, gentamicin-loaded AuNCs conjugated to an antibody targeting a conserved outer membrane protein were highly effective against P. aeruginosa biofilms. Conclusions: These results confirm the therapeutic versatility of our approach. However, to the extent that its synergistic efficacy is dependent on the ability to achieve both a lethal photothermal effect and the thermally controlled release of a sufficient amount of antibiotic, they also demonstrate the importance of carefully designing appropriate antibody and antibiotic combinations to achieve the desired therapeutic synergy.